Jews, Catholics, and the burden of history - Lederhendler, Eli (Studies in contemporary Jewry, 2005)
Volume XXI of the distinguished annual Studies in Contemporary Jewry marks sixty years since the end of the Second World War and forty years since the Second Vatican Council's efforts to revamp Church relations with the Jewish people and the Jewish faith. Jews, Catholics, and the Burden ofHistory offers a collection of new scholarship on the nature of the Jewish-Catholic encounter between 1945 and 2005, with an emphasis on how this relationship has emerged from the shadow of the Holocaust.